Calcined Green Mussel Shell Waste as a Bioaggregate in Pervious Concrete Paver Blocks - Muhammad Sholeh Arifin; Ika Bagus Priyambada; Budi Prasetyo Samadikun; Sheikh Kamran Abid (Universitas Diponegoro, 2026)
Ineffective management of green mussel shell waste could worsen environmental problems. Green mussel shell waste can be used as bioaggregate, because it contains 90% CaCO3, the content is similar to limestone, which is generally chemically inert. Seashells calcined at high temperatures and fine particle size can show limited reactivity. The purpose of this study was to determine the amount of green mussel shell waste production and to determine the optimal proportion of calcined green mussel shell (GMS) bioaggregate in pervious concrete paver blocks (PCPB). The methods used were observational to calculate the amount of waste produced over 8 consecutive days and experimental to determine the mechanical and physical performance of pervious concrete paver blocks with bioaggregate substitution levels of 0%, 6%, 12%, 18%, and 24% at a test age of 28 days. The pervious concrete paver blocks were molded using an automatic hydraulic press machine that was vibrated for 10 seconds, with a mold size of 21 x 10.5 x 6 cm. The testing included the constituent materials and test specimens in accordance with the standards. Green mussel shell waste production during the 2025 planting season was 87.27 kg/day. The test results showed that the compressive strength, porosity, and permeability coefficient values were within the range recommended by ACI 522R-10 2010 and SNI 03-0691-1996 for permeable concrete used as pavement material.